Two axiidean ghost shrimps (Crustacea: Decapoda) from India, Guyanacaris keralam sp. nov. (Axiidae) and Paragourretia galathea (K. Sakai, 2017) (Ctenochelidae) - Padate, Vinay P.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zootaxa, 2022)
Ghost shrimps collected from the Indian Exclusive Economic Zone by the Fishery Oceanographic Research Vessel Sagar Sampada during two cruises in the eastern (105 metres depth) and southeastern Arabian Sea (101 and 326 metres depth) were studied. One male, identified as Guyanacaris keralam sp. nov. of the Axiidae, differs from its congeners in the unique armature of the rostrum, gastric region of carapace, pleonal pleural margins, dorsal margins of cheliped fingers, ventral margin of second pereopod merus, and lateral margins of telson; the presence of corneous spines on the propodi and dactyli of third and fourth pereopods, and the relative sizes of the ocular peduncles, antennular peduncle, scaphocerite and cheliped fingers. Guyanacaris K. Sakai, 2011 is re-diagnosed based on the presence of short supraocular spine and post-cervical carina on carapace, dentate margins of first two pleonal pleura, third to fifth pleura with angular to straight posterior margins, antennal scaphocerite with mesial spine at base, and presence of male first pleopod 1. Bruceaxius thailandensis K. Sakai, 2015 is tentatively retained in Bruceaxius K. Sakai, 2011, owing to absence of mesial spine at the base of scaphocerite, tuberculate upper margins of carpus, propodus and dactylus of major cheliped, and tri-segmented appendix masculina on male second pleopod. In addition, two males, diagnosed herein as Paragourretia galathea (K. Sakai, 2017) of the Ctenochelidae, differ from the holotype female only in the relative length of the terminal antennular article and the presence of a distomedian spinule on the telson, of all the features.